Analisis Jenis dan Kandungan Makanan Oreochromis mossambicus dan Oreochromis nilotica asal Danau Lindu - Syech Zainal; Manap Trianto; Novalina Serdiati; Raya Agni (Media Eksakta, 2023)
The purpose of this study was to describe the type and content of food for Mujair and tilapia fish from Lake Lindu by means of a section and taking gastric contents and observing and analyzing them. The stages of the research were fish sampling, surgery (section), research in the laboratory and testing the nutritional content of food (carbohydrates, protein and fat). The research samples were Mujair fish (Oreochromis mossambicus) and Tilapia (Oreochromis nilotica) from Lake Lindu. Based on research obtained by the types of fish food O. mossambicus obtained two groups of Phytoplankton namely, Oedogonium sp, Anabaena sp, Nostoc sp, Oscillatoria princeps, Diatomae sp, Navicula gysingen, Rivularia sp, Coelastrum sphaericum, and Zooplankton namely Chironomus sp, Dugesia tigrina. There were eight types of food for O. nilotica, consisting of six types of phytoplankton, namely Oedogonium sp, Anabaena sp, Nostoc sp, Oscillatoria princeps, Rivularia sp, Coelastrum sphaericum and 2 types of zooplankton feed, namely Chironomus sp and Dugesia tigrina. The nutritional content of fish food/feed is protein (15.18%), fat (19.20%), and carbohydrates (1.9%).